Autonomous radio link for data transmission for sensors in high mountains: a case study Laguna Palcacocha, Huaraz – Ancash – Peru - Alvarado Cáceres, Luis Ruperto (2023)
The study proposes the radio link, powered by photovoltaic solar energy, using wireless radios. The system allows the transmission of data for sensors located in high mountains. For the design, the Ubiquiti simulator was used, verifying the coordinates of the radio stations, evaluating the lines of sight between the separate stations. The total distance between Base Station B and Sensor Station S is approximately 23,852 Kilometers, with 04 radio links, in the free 5.8 Ghz band. This system allows a continuous operation of 24 hours with low levels of solar radiation energy, additionally it can support HD, IP video cameras.